Anterior Palatoplasty for Obstructive Sleep Apnea: A Systematic Review and Meta‐analysis. (31st October 2017) - Binar, Murat; Karakoc, Omer
Abstract : Objective: The aim of this study was to determine the general outcomes and surgical success rates of anterior palatoplasty (AP) in patients with obstructive sleep apnea (OSA). Data Sources: A systematic review of the literature and meta‐analysis of published data were performed by searching the Cochrane, SAGE, MEDLINE, and Google Scholar databases, from January 1, 2007, to March 27, 2017, using relevant keywords. Review Methods: The search scanned for studies with patients who had undergone AP (with or without tonsillectomy) as a single‐stage, single‐level surgical intervention for treatment of OSA. Two independent reviewers (M.B. and O.K.) inspected titles and abstracts of the studies according to established criteria. The full texts were then reviewed to extract the clinical and polysomnographic data. The primary outcome was the surgical success rate, defined as a reduction in the apnea‐hypopnea index (AHI) of 50% or greater and an AHI of less than 20 postoperatively. The PRISMA statement was followed. Results: After systematic evaluation of potentially relevant articles, 14 studies were downloaded, and 6 studies, consisting of 170 patients, met the study criteria. A fixed effects model was used to analyze the data. The surgical success rate of AP was 60.6%. No serious complications were reported in the literature. Conclusion: The results of the present meta‐analysis support AP as a moderately effective surgical method for the treatment of OSA. Comparative and randomized controlled prospective studies showing long‐term results, with pre‐ and postoperative data, should be conducted to demonstrate the exact outcomes and reliability of this surgical technique.